DEVELOPMENT OF FOOD SPOILAGE INDICATOR FOR DAIRY PRODUCTS USING ANTHOCYANIN EXTRACTED FROM HYLOCEREUS POLYRHIZUS - M. Tamilarasi; B. Murugan; I. Manikkavasagan; S. Meignanalakshmi; S.K. Mathanghi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Intelligent spoilage indicators are the emerging area of food packaging sector as it can provide information on quality of food during storage and transportation. The present research work was aimed to develop an anthocyanin based food spoilage indicator to detect spoilage in dairy products. Anthocyanin was extracted from the peels of dragon fruit, incorporated into filter paper and used as food spoilage sensing agent. Dragon fruit peel extract showed a characteristic peak of absorption at 537nm and was found to have 141.21±3.9 mg/g of total anthocyanin content and 46.8 ± 0.98 mg/g GAE of phenolic compounds. The pH sensitivity of the dragon fruit peel extract and indicator film were quite similar with the colour change from red to yellow as the pH increases. The indicator film was effective insignalling the quality deteriorations occurring in stored paneer and khoa.